Oestradiol Differentially Influences Feeding Behaviour Depending on Diet Composition in Female Rhesus Monkeys. (18th July 2013) - Johnson, Z. P.; Lowe, J.; Michopoulos, V.; Moore, C. J.; Wilson, M. E.; Toufexis, D.
<x xml:space="preserve">Abstract</x> In females, cyclical changes in the ovarian hormone oestradiol are known to modulate feeding behaviour. However, what is less clear is how these behavioural effects of oestradiol are modified by the macronutrient content of a diet. In the present study, we report data showing that oestradiol treatment results in both significantly smaller meals and a reduced total calorie intake in ovariectomised, socially‐housed female rhesus macaques when only chow diet is available. Conversely, during a choice dietary condition where both palatable and chow options are available, oestradiol treatment had no observable, attenuating effect on calorie intake. During this choice dietary phase, all animals consumed more of the palatable diet than chow diet; however, oestradiol treatment appeared to further increase preference for the palatable diet. Finally, oestradiol treatment increased snacking behaviour (i.e. the consumption of calories outside of empirically defined meals), regardless of diet condition. These findings illustrate how oestradiol differentially influences feeding behaviour depending on the dietary environment and provides a framework in which we can begin to examine the mechanisms underlying these observed changes.